2018
DOI: 10.1163/9789004369900
|View full text |Cite
|
Sign up to set email alerts
|

Atlas of Religion in China: Social and Geographical Contexts

Abstract: Disclaimer: The maps in this atlas are solely for the scholarly purpose of visualizing characteristics of topography, population, and religious venues. None of the maps should be taken as an official demarcation of territories or borders by any political or religious organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(7 citation statements)
references
References 95 publications
1
6
0
Order By: Relevance
“…In addition, no Taoist and Buddhist sacred mountains are found in places in Northwest China, such as Xinjiang, which is more influenced by Islam, and which brought Taoism and Chinese Buddhism closer to the centre-south of China (Dillon, 2003). Such geographical distribution is consistent with the Atlas of Religion in China (Yang, 2018).…”
Section: Geographical Distribution Of Sacred Mountainssupporting
confidence: 88%
“…In addition, no Taoist and Buddhist sacred mountains are found in places in Northwest China, such as Xinjiang, which is more influenced by Islam, and which brought Taoism and Chinese Buddhism closer to the centre-south of China (Dillon, 2003). Such geographical distribution is consistent with the Atlas of Religion in China (Yang, 2018).…”
Section: Geographical Distribution Of Sacred Mountainssupporting
confidence: 88%
“…For example, one study finds an uptick in the self‐reported importance of religion in people's lives in China during the 1990s, followed by stability in the 2000s (Hu 2017). Yang (2014:567, 2018) has similarly reported the occurrence of some religious revival in China, following the 1966–79 period when religious practice was forbidden and “all temples, mosques, and churches were closed down.” But there have not been similar studies on most Asian or African countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the establishment of the People's Republic of China, Marxism prevails and has become the new orthodoxy in mainland China, and thus atheism, materialism, and scientism are taught through the entire education system (Yang 1999). Under Mao's leadership and particularly during the Cultural revolution (1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973)(1974)(1975)(1976), religious beliefs were proclaimed as 'feudal superstition', religious organisations were banned, and religious activities were widely prohibited (Yang 2018). Owing to China's opening and reform in 1980s, religious freedom was written into the Chinese constitution with an aim to promote spiritual revival and development and regulate faith practices (The Law Library of Congress 2018).…”
Section: Religious and Cultural Landscape Of Chinamentioning
confidence: 99%